Analysis Business Development Strategy UMKM Singkong Keju Argotelo Salatiga Through Business Model Canvas Method - Nafi Addin Pramesti; Hari Susanta Nugraha; Ngatno Ngatno (Universitas Diponegoro, 2024)
Abstract: The problem in this research is that the development of Argotelo’s business is still stagnating and even declining. This is due to the lack of a good business development model plan for Argotelo. The aim of this research is to formulate an overview of Argotelo’s current business model through Business Model Canvas method and formulate recommendation for business development strategies that can be applied to Argotelo. The research used qualitative case descriptive methods with interviews, obeservations, and documentation to obtain data in the field. Research results suggest that in order to develop its products or create new products and expand segmentation as well as marketing reach followed by promotion and research and development. Besides, in order to sustain and thrive, Argotelo needs to optimize its strengths and potential as well as correct its shortcomings and constraints.Keyword: business development; business model canvas; ansoff’s matrixAbstrak: Permasalahan dalam penelitian ini dikarenakan pengembangan bisnis Argotelo masih mengalami stagnasi perkembangan dan bahkan menurun. Hal tersebut disebabkan karena belum adanya rencana model pengembangan bisnis ke depan yang baik pada Argotelo. Tujuan penelitian ini adalah untuk merumuskan gambaran model bisnis Argotelo saat ini melalui metode Business Model Canvas dan merumuskan rekomendasi strategi pengembangan bisnis yang dapat diterapkan untuk Argotelo. Penelitian ini menggunakan metode kualitatif deskriptif kasus dengan wawancara, observasi, dan dokumentasi untuk memperoleh data di lapangan. Hasil penelitian menunjukkan untuk mengembangkan bisnisnya ke depan, Argotelo perlu untuk mengembangkan produknya atau membuat produk baru dan memperluas segmentasi serta jangkauan pemasaran yang diikuti dengan promosi dan riset lapangan dan pengembangan. Selain itu juga supaya tetap sustain dan berkembang, Argotelo perlu untuk mengoptimalkan kekuatan dan potensi yang dimiliki serta memperbaiki kekurangan dan kendala yang terjadi.Kata kunci: pengembangan bisnis; business model canvas; ansoff’s matrix